Physical Quality and Organoleptic Testing of Golden Apple Snail Pomacea canaliculata) Mucus Gel as a Burn Treatment - Fadhilah, Diana; Nadjmir, Mikail; Adilla, Ardis Trianita; Santoso, Putra; Maliza, Rita (Jurnal Biologi Tropis, 2024)
Golden Apple Snail (Pomacea canaliculata) secretion has traditionally been used for wound healing due to its high protein content, which promotes cell regeneration and inhibits inflammation. This study aims to utilize this secretion to formulate a topical gel for burn treatment, providing a controlled use for the abundant, invasive species in agricultural areas. Gel formulations with varying secretion concentrations (10%, 15%, and 20%) were evaluated for organoleptic properties, homogeneity, pH, adhesion, spreadability, and viscosity. Results indicated that all formulations were homogeneous and had pH values within the acceptable range (4.5-6.5). The 15% secretion gel showed the highest user acceptance and optimal balance between spreadability and adhesion, but all formulations had higher than standard viscosity and lower spreadability. Adjusting carbopol concentration is recommended to improve the gel's physical properties. The 15% formulation is the most promising for effective topical application.